Modelling the flexibility of production systems in Industry 4.0 for analysing their productivity and availability with high-level Petri nets. Issue 1 (July 2017) - Long, F.; Zeiler, P.; Bertsche, B.
Abstract: Industry 4.0 is characterized by a strong individualization of products under the conditions of a highly flexible production. The customer-oriented production leads directly to complex flexible production systems, which need to be modelled and optimized. Analysing the availability of flexible production systems in Industry 4.0 aims to reduce the risks of unexpected machine failure and thus resulting losses, and subsequently to support the optimization of production systems. Extended coloured stochastic Petri nets are used in this paper to build a model for modelling a flexible production system with three machines. The results show that flexible production can be simulated with this model.